2016
DOI: 10.1097/txd.0000000000000582
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Calciphylaxis in a Kidney Transplant Patient

Abstract: IntroductionCalciphylaxis is a rare and often fatal condition mostly associated with end-stage renal disease. The pathophysiology remains elusive and treatment options are scarce. We present a rare case of severe calciphylaxis after kidney transplantation in a patient with persistent hyperparathyroidism.Case descriptionA 78-year-old man with a history of end-stage renal disease developed edema and ulcerations on both lower limbs 14 months after kidney transplantation while receiving an mammalian target of rapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…This has lead to the trial of alternative, less invasive options including oxygen therapy, corticosteroids (for non‐ulcerating lesions at low risk for infection), sodium thiosulfate and cinacalcet. Although some of these noninvasive therapies have meant some patients have avoided parathyroidectomy, there is limited evidence for their efficacy or recurrence rates for calciphylaxis (Table ) …”
Section: Discussionmentioning
confidence: 99%
“…This has lead to the trial of alternative, less invasive options including oxygen therapy, corticosteroids (for non‐ulcerating lesions at low risk for infection), sodium thiosulfate and cinacalcet. Although some of these noninvasive therapies have meant some patients have avoided parathyroidectomy, there is limited evidence for their efficacy or recurrence rates for calciphylaxis (Table ) …”
Section: Discussionmentioning
confidence: 99%
“…Proposed methods of preventing calciphylaxis include managing comorbid conditions, such as diabetes mellitus, chronic kidney disease, and obesity, as well as decreasing calcium supplements and using non-calcium-based renal supplements 6,7. Previous case reports cite the resolution of cutaneous calciphylaxis after kidney transplantation 8,9. On the basis of the existing literature, this unfortunate complication of hemodialysis may have been prevented by a kidney transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Nordheim et al further suggested that normal kidney graft function was imperative for cure after transplantation. Despite this, a case of calciphylaxis occurring after kidney transplant in a patient with normal graft function has also been reported, and predictive factors for the development and/or resolution of this disorder have yet to be identified …”
Section: Transplant Outcomesmentioning
confidence: 99%
“…Reports exist of patients being cured of calciphylaxis after kidney transplantation . Conversely, there are case reports of patients developing calciphylaxis after kidney transplant as well as simultaneous liver‐kidney (SLK) transplant . We review calciphylaxis and summarize the published experience of the relationship between calciphylaxis and liver, kidney, and SLK transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation